Clinical report of Mediterranean fever in a child in Ukraine – Don’t miss it! - К.Y. Pashenko; Т.V. Frolova; Y.V. Кarpushenko; G.R. Muratov; О.М. Savvo; Т.О. Khalturina; О.М. Ashcheulov (Сучасна педіатрія: Україна)
Introduction. Familial Mediterranean fever (FMF) is a non-infectious genetic disease caused by a mutation in the MEFV gene. This disease is more common in people of Mediterranean or Middle Eastern descent, but can occur in any ethnic group, including those living European countries. FMF has typical clinical symptoms. Its long term without appropriate treatment the disease can lead to a violation of the child's physical development and result in the development of amyloidosis.